Analysis of The Sagi Traditional Boxing Tradition of The Libunio Community in Soa District as A Means of Character Education in Physical Education Learning at Schools - Wani, Bernabas; Bate, Nikodemus; Adrianus Alfaro Ewa (Universitas PGRI Palembang, 2024)
This research aims to analyze the traditional Sagi boxing tradition in the Libunio community, Soa District, as a means of character education in physical education learning at schools. The traditional Sagi boxing is an essential part of the cultural heritage of the Libunio community, passed down from generation to generation. In the Sagi traditional boxing ceremony, there are many systems and rules that must be followed by the indigenous people of Libunio, Soa District, Ngada Regency This ceremony also has several stages or implementation processes that demonstrate the importance of culture as a foundation in preserving local wisdom. This tradition is built based on the needs of the community, considering activities that have been fostered from generation to generation. This research is urgent due to the need to revive and utilize the Sagi traditional boxing tradition as a means of character education in schools. Character education is increasingly necessary to face the complex moral and social challenges in society. Through the integration of character values in the Sagi traditional boxing tradition, such as discipline, courage, honesty, strong determination, respect for opponents, and mutual respect, it is expected to positively contribute to the development of students' character through physical education learning in schools. The research method used is a qualitative approach with observation, interview, and document analysis techniques. Observations were conducted to understand the practice of Sagi traditional boxing directly, while interviews were conducted with community leaders and education experts to gain a deep understanding. Document analysis was carried out on literature related to the Sagi traditional boxing tradition and character education. Based on the observation results, the Sagi traditional boxing in Libunio Village shows discipline, courage, honesty, strong determination, respect for opponents, and mutual respect, so this research can serve as a reference for implementing character education in schools that apply the Sagi traditional boxing tradition